Attenuating Effect of Chlorella Extract on NLRP3 Inflammasome Activation by Mitochondrial Reactive Oxygen Species - Nakashima, Yuya; Gotoh, Kazuhito; Mizuguchi, Soichi; Setoyama, Daiki; Takata, Yurie; Kanno, Toshihiro; Kang, Dongchon (Frontiers in Nutrition, 2021)
The NOD-like receptor family, pyrin domain-containing protein 3 (NLRP3) inflammasome has been linked to the pathogenesis of a wide variety of human diseases. Although many drugs and inhibitors have been developed to treat NLRP3-associated diseases, only limited clinical data support their efficacy and safety. Chlorella, a unicellular green alga that is widely and safely used as a food supplement, contains various antioxidants. In this study, we obtained a fat-soluble extract from Chlorella (CE) and demonstrated that it reduced NLRP3 inflammasome activation by inhibiting mitochondrial reactive oxygen species and caspase-1 activation. In addition, CE supplementation attenuated lipopolysaccharide-induced interleukin 1β transcription through activation of hypoxia-inducible factor 1a in vitro and in vivo. As Chlorella is a safe and useful food supplement, it may be a practical pharmacological approach for treating NLRP3-driven diseases.